Using Gene Expression to Study Specialized Metabolism—A Practical Guide - Delli-Ponti, Riccardo; Shivhare, Devendra; Mutwil, Marek (Frontiers in Plant Science, 2021)
Plants produce a vast array of chemical compounds that we use as medicines and flavors, but these compounds' biosynthetic pathways are still poorly understood. This paucity precludes us from modifying, improving, and mass-producing these specialized metabolites in suitable bioreactors. Many of the specialized metabolites are expressed in a narrow range of organs, tissues, and cell types, suggesting a tight regulation of the responsible biosynthetic pathways. Fortunately, with unprecedented ease of generating gene expression data and with >200,000 publicly available RNA sequencing samples, we are now able to study the expression of genes from hundreds of plant species. This review demonstrates how gene expression can elucidate the biosynthetic pathways by mining organ-specific genes, gene expression clusters, and applying various types of coexpression analyses. To empower biologists to perform these analyses, we showcase these analyses using recently published, user-friendly tools. Finally, we analyze the performance of coexpression networks. While valuable, we show that coexpression analysis cannot fully substitute other computational approaches in the inference of biosynthetic pathways of specialized metabolism.